Optimal Transparency in a Dealer Market with an Application to Foreign Exchange - Lyons, Richard K. (Journal of Financial Intermediation, 1996)
This paper addresses a fundamental trade-off in the design of multiple-dealer markets. Namely, though greater transparency can accelerate revelation of information in price, it can also impede dealer risk management. If dealers could choose the transparency regime ex ante, which regime would they choose? We show that dealers prefer incomplete transparency (meaning marketwide order flow is observed with noise). Slower price adjustment provides time for nondealers to trade, thereby sharing risk otherwise borne by dealers. At some point, however, further reduction in transparency impedes risk sharing: too noisy a public signal provides nondealers too little information to induce them to trade.Journal of Economic LiteratureClassification Numbers: F31, G15.